Bilingualism and multilingualism on pluralism in English Language Teaching (ELT): Bibliometric analysis - Fitriyah, Diana Indah; Hamida, Wanda; Afifah, Muthiah; Nurhayati, Lusi (Universitas Muhammadiyah Sidoarjo, 2026)
The appearance of multicultural societies and globalization as the problems in the field of English Language Teaching (ELT). Moreover, pluralism is used in the education system to support the belief that a variety of languages and cultures should be implemented in the teaching and learning process. Despite the growing attention to pluralism, comprehensive bibliometric analysis mapping this research domain remain limited. Therefore, this study conducted a bibliometric analysis, using statistical publication for assessing publications. It presents the most productive authors, countries, sources, and most cited articles. This study analyzed 98 articles, which were guaranteed to be impartial in their interpretive results. The data analysis is collected in Scopus and was analyzed using R.4.4.1 and VOS viewer to get the exact pattern. The results show that the United Kingdom stands as the highest published article, and HO WYJ and FUSTER C are the authors who show the impact leader. In addition, the International Journal of Bilingual Education and Bilingualism had the most publications, closely followed by the International Journal of Multilingualism. Keyword co-occurrence analysis showed that “multilingual” occupies a central position in the network visualization, indicating its pivotal role in pluralism-related research. These findings provide an overview of the state of pluralism studies in ELT and highlight the need for future research that explores specific pedagogical implementations and the role of digital technologies in promoting inclusive and culturally responsive language education. For ELT practitioners in Indonesia, these findings offer practical insights into integrating multilingual and culturally responsive approaches into classroom practices to better address diverse student backgrounds and learning needs.